Pentraxins in the activation and regulation of innate immunity. Issue 1 (November 2016) - Daigo, Kenji; Inforzato, Antonio; Barajon, Isabella; Garlanda, Cecilia; Bottazzi, Barbara; Meri, Seppo; Mantovani, Alberto
Summary: Humoral fluid phase pattern recognition molecules (PRMs) are a key component of the activation and regulation of innate immunity. Humoral PRMs are diverse. We focused on the long pentraxin PTX3 as a paradigmatic example of fluid phase PRMs. PTX3 acts as a functional ancestor of antibodies and plays a non‐redundant role in resistance against selected microbes in mouse and man and in the regulation of inflammation. This molecule interacts with complement components, thus modulating complement activation. In particular, PTX3 regulates complement‐driven macrophage‐mediated tumor progression, acting as an extrinsic oncosuppressor in preclinical models and selected human tumors. Evidence collected over the years suggests that PTX3 is a biomarker and potential therapeutic agent in humans, and pave the way to translation of this molecule into the clinic.